Batik Pattern Representation of SITR Mathematical Model on Tuberculosis Transmission in Aceh Province - Wisesa, Gicela Viga Gita; Sholichati, Jamila Maulida; Rahmadhanie, Riska Fajry; Sugiyanto, Sugiyanto (Proceeding International Conference on Religion, Science and Education, 2026)
Mycobacterium tuberculosis is the causative agent of tuberculosis (TB), which continues to rank among the most dangerous infectious diseases in Aceh Province. In order to characterize the dynamics of TB transmission, treatment, and recovery, this study intends to develop and evaluate the stability of the SITR (Susceptible–Infectious–Treatment–Recovery) mathematical model. Four compartments are created by the model: susceptible, infectious, treatment, and recovery. The Aceh Provincial Health Office provided secondary data. The basic reproduction number (R0) and the disease-free and endemic equilibrium points were determined in order to conduct the stability analysis. The findings demonstrate that the SITR model has two equilibrium points and maintains stability when there is no sickness, with R0 = 0.124, suggesting that there isn’t a population breakout. Additionally, to graphically depict the dynamics of TB transmission and recovery in Aceh, the model simulation was converted into a batik motif design. As a result of the disease’s controlled spread, the number of susceptible people gradually declines over time, while the number of people receiving treatment and recovering rises. These results show that the SITR model has possibilities for imaginative visualization using traditional art forms like batik in addition to offering a trustworthy analytical foundation for illness modeling.